2018
DOI: 10.1007/978-3-319-76735-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management in Early OA

Abstract: Knee osteoarthritis affects an important percentage of the population throughout their life. Several factors seem to be related to the development of knee osteoarthritis including genetic predisposition, gender, age, meniscal deficiency, lower limb malalignments, joint instability, cartilage defects, and increasing sports participation. The latter has contributed to a higher prevalence of early onset of knee osteoarthritis at younger ages with this active population demanding more consistent and durable outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…Knee osteoarthritis (KOA) is the most common degenerative joint lesion; it has a high prevalence and a negative impact on the quality of life of affected individuals ( 1 ). It has been reported in a case–control study carried out in North Staffordshire that 9.6% of men and 18% of women have symptomatic KOA at the age of 60 years and over ( 2 ).…”
mentioning
confidence: 99%
“…Knee osteoarthritis (KOA) is the most common degenerative joint lesion; it has a high prevalence and a negative impact on the quality of life of affected individuals ( 1 ). It has been reported in a case–control study carried out in North Staffordshire that 9.6% of men and 18% of women have symptomatic KOA at the age of 60 years and over ( 2 ).…”
mentioning
confidence: 99%
“…Women have twice the risk of developing bilateral knee OA than men and have 2.6 times greater chance of developing hand OA. 24 This difference is credited to anatomic factors, such as having a thinner articular cartilage layer, a three-degree-higher anatomic axial knee angle (Q angle), and a narrower distal femur than men. 24 Menopause is another possible cause, many studies showing that articular cartilage is sensitive to estrogen deprivation.…”
Section: Figure 1 Dalys Age-standardized Over Timementioning
confidence: 99%
“…24 This difference is credited to anatomic factors, such as having a thinner articular cartilage layer, a three-degree-higher anatomic axial knee angle (Q angle), and a narrower distal femur than men. 24 Menopause is another possible cause, many studies showing that articular cartilage is sensitive to estrogen deprivation. It has also been demonstrated that for each additional childbirth, women have a 2% increment in the risk for hip arthroplasty (95% CI 1-4) and of 8% (95% CI 6-10) for knee arthroplasty.…”
Section: Figure 1 Dalys Age-standardized Over Timementioning
confidence: 99%
“…This cost-effectiveness finding supports the use of IA-HA in patients with early and moderate knee OA, as the benefits of IA-HA are apparent within the patient population with mild to moderate knee OA. pharmacological management of knee OA often includes education and self-management, weight loss and strengthening, and biomechanical interventions such as knee braces [11][12][13]. Anti-inflammatories are recommended for patients with symptomatic OA of the knee to address pain; however, prolonged use of NSAIDS increases risk of gastrointestinal (GI), cardiovascular, and renal complications [14,15].…”
Section: Key Summary Pointsmentioning
confidence: 99%